1995
DOI: 10.1093/tropej/41.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Cutaneous Leishmaniasis in Rural Ecuadorian Children

Abstract: The relationship between nutritional status and cutaneous leishmaniasis (CL) was evaluated in 230 children living in a rural subtropical rainforest in Northwest Ecuador. One-third of the subjects had evidence of either current (13 per cent) or past CL infection (21 per cent). Subjects with current (4.71 +/- 0.44 mg) or previous disease (4.29 +/- 0.35 mg) had lower mean daily dietary iron intakes than non-infected children (5.45 +/- 0.2 mg; chi 2 = 0.048), but not energy, protein, or other micronutrients. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
14
0
3
Order By: Relevance
“…Low height/age z-scores can be used to identify children at risk of stunting [37, 38], and is a robust measure for population nutritional studies [39, 40]. Few studies have confirmed the relationship between malnutrition and risk of Leishmania infection [41, 42] and a small study in adults did not find a relationship between weight and time-to-cure in tegumentary leishmaniasis [43]. However, using this indicator, we provide evidence of the influence of nutrition on treatment response in children with CL, as has been described in other infectious diseases [44, 45], murine models of leishmaniasis [46], and in a small descriptive study conducted in children treated with miltefosine [47].…”
Section: Discussionmentioning
confidence: 99%
“…Low height/age z-scores can be used to identify children at risk of stunting [37, 38], and is a robust measure for population nutritional studies [39, 40]. Few studies have confirmed the relationship between malnutrition and risk of Leishmania infection [41, 42] and a small study in adults did not find a relationship between weight and time-to-cure in tegumentary leishmaniasis [43]. However, using this indicator, we provide evidence of the influence of nutrition on treatment response in children with CL, as has been described in other infectious diseases [44, 45], murine models of leishmaniasis [46], and in a small descriptive study conducted in children treated with miltefosine [47].…”
Section: Discussionmentioning
confidence: 99%
“…Infection is also known to be dependent on host nutritional status and acquired immunosupression (e.g. HIV) [21],[22]. Risk factors of disease commonly include sex (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the lowlands are children under the age of ten in tropical and five years in subtropical Pacific region , Armijos et al 1997. The increased disease prevalence in children could be associated with no previous exposure to the parasite, the role of cellular immune status and/or with malnutrition (Weigel et al 1995). Nevertheless, for the Amazon region in a passive hospital-based report the mean age of leishmaniasis diagnosis was 33.4 and 19.7 years for MCL and CL respectively (Amunarriz 1991), suggesting unknown reasons for delays in the diagnosis in this wide and disperse region.…”
Section: Age Gender and Body Distribution Of Lesionsmentioning
confidence: 99%